Predicting urges for non-suicidal self-injury using cardiac autonomic indices in outpatient adolescents: a pilot ecological momentary assessment study - Driesch, Luisa von den; Koenig, Julian; Reichl, Corinna; Sigrist, Christine; Sele, Silvano; Kaess, Michael (Journal of affective disorders, 2026)
Aims - The purpose of the present study was to examine cardiac autonomic indices as potential short-term predictors of non-suicidal self-injury (NSSI) urges and NSSI incidents in adolescents at high risk for NSSI. - Methods - The sample consisted of 29 female adolescents with NSSI aged 13-17 years recruited from a specialized outpatient clinic for adolescent risk-taking and self-harming behavior. During one weekend, participants wore an ECG belt that continuously recorded data on heart rate (HR), heart rate variability (HRV) and accelerometry. They also completed hourly ecological momentary assessments, reporting on NSSI incidents, NSSI urge, and momentary affect. Dynamic structural equation modeling was used to analyze temporal associations, including the examination of cross-lagged effects. - Results - 14 acts of NSSI were reported by 6 participants (20.7 % of the sample). Due to low intra-individual variance in NSSI, models including NSSI incidents did not converge reliably. After controlling for preceding negative affect, a significant negative effect of HR and a positive effect of HRV on NSSI urge were found (i.e. lower HR and higher HRV predicted stronger NSSI urge). - Discussion - These findings provide initial evidence of autonomic dysregulation at the individual level preceding increases in NSSI urge and underscore the potential of combining subjective and physiological indicators to improve prediction of NSSI urge. Future studies should explore whether this approach also enhances the prediction of NSSI incidents.